Comparison of the effectiveness of lecture instruction and virtual reality-based serious gaming instruction on the medical students’ learning outcome about approach to coma - Mansoory, Meysam Siyah; Khazaei, Mohammad Rasool; Azizi, Seyyed Mohsen; Niromand, Elham (BMC medical education, 2021)
Background New approaches to e-learning and the use of virtual reality technology and serious game in medical education are on the rise. Therefore, the purpose of this study was to compare the effectiveness of lecture method and virtual reality-based serious gaming (VRBSG) method on students learning outcomes about the approach to coma. Methods We adopted a randomized trial method for this study and selected 50 medical students dividing them into experimental and control groups. Students’ learning outcome was measured with a 10-item test. Serious game usability scale was used to evaluate the usability of the serious game. Descriptive and inferential statistics were used for data analysis by SPSS-22 software. Results Students’ familiarity with e-learning and VRBSG was low. The mean usability of a VRBSG was 126.78 ± 10.34 out of 150. The majority of students were eager to be instructed through VRBSG. The mean score of learning outcomes in the experimental group was significantly higher than the control group (t = − 2.457, P = 0.019). Conclusion Students’ learning outcomes in the VRBSG group in the test approach to coma were significantly better than the lecture group. The usability of the serious game instruction method was high. Taken together, instruction through VRBSG had an effective role in medical students’ learning.